2014
DOI: 10.1007/s00438-014-0811-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative phylogenetic analysis of genome-wide Mlo gene family members from Glycine max and Arabidopsis thaliana

Abstract: Powdery mildew locus O (Mlo) gene family is one of the largest seven transmembrane protein-encoding gene families. The Mlo proteins act as negative regulators of powdery mildew resistance and a loss-of-function mutation in Mlo is known to confer broad-spectrum resistance to powdery mildew. In addition, the Mlo gene family members are known to participate in various developmental and biotic and abiotic stress response-related pathways. Therefore, a genome-wide similarity search using the characterized Mlo prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 52 publications
4
43
0
Order By: Relevance
“…4C). The serine-rich domain is a common protein motif involved in defense responses, abiotic stress, growth regulation, wounding, and plant development (Sripinyowanich et al , 2013; Deshmukh et al , 2014). The serine-rich domain is also found in the products of the Porteresia coarctata serine - rich - protein ( PcSrp ) and Capsicum annuum RING - finger protein 1 ( CaRFP1 ) genes, whose functions are dependent on salinity and biotic stress conditions, respectively (Mahalakshmi et al , 2006; Hong et al , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…4C). The serine-rich domain is a common protein motif involved in defense responses, abiotic stress, growth regulation, wounding, and plant development (Sripinyowanich et al , 2013; Deshmukh et al , 2014). The serine-rich domain is also found in the products of the Porteresia coarctata serine - rich - protein ( PcSrp ) and Capsicum annuum RING - finger protein 1 ( CaRFP1 ) genes, whose functions are dependent on salinity and biotic stress conditions, respectively (Mahalakshmi et al , 2006; Hong et al , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Mlo interacts with calmodulin in vitro and requires calmodulin, but not heterotrimeric G-proteins, to function (Kim et al, 2002b;Lorek et al, 2013). To date,15,17,9,12,and 39 Mlo paralogs have been reported in the genomes of Arabidopsis, grape, maize, rice and soybean, respectively (Consonni et al, 2006;Devoto et al, 2003;Feechan et al, 2008;Liu and Zhu, 2008;Deshmukh et al, 2014). Phylogenetic analysis using 17 members of grape Mlo gene family and members from rice, barley, tomato, maize, wheat, and Arabidopsis, resulted in the formation of six clades with clade VI containing AtMlo3, which in previous analyses was identified as a single divergent lineage (Feechan et al, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…The medium size gene family MLO are variably distributed and 39, 15, 17, 12, 21, 13 and 38 MLO genes were noticed in soybean, Arabidopsis, grape, rice, apple, cucumber, and cotton, respectively [8,10,13,26,36,42,44]. MLO genes have been thoroughly studied both in many monocots and dicots.…”
Section: Introductionmentioning
confidence: 99%